PROSPECTIVE ZONE AREA FOR AGRICULTURE AND RESIDENTIAL BASED ON GEOLOGICAL DISASTER POTENTIALS IN SOUTH BANDUNG REGION - SULAKSANA, NANA; Isandarsyah, Teuku Yan Waliana Muda; Rifai, Achmad; Raditya Rendra, Pradnya Paramarta; Sulastri, Murni (Journal of Geological Sciences and Applied Geology, 2019)
The number of residents in Bandung continues to increase every year, especially in the southern part of Bandung. The development of residential areas needs to get attention from the local government and people in Bandung, especially to evaluate various geological hazards such as floods, landslide, earthquake, and other. Research methodolgy is qualitative method by interviewing local community and analyzing landsat image using Google Earth and Digital Earth Model (DEM) image to know land use in the research area. In addition, quantitative methods are also used with superimposed manual statistical analysis and weighting methods using Microsoft Excel, Global Mapper, and Mapinfo software. The result of research shows that South Bandung area has Land Suitability Score > 130 (Residential Area) and Land Suitability Score > 135 (Agriculture Area) which are categorized as very good settlement and education area; Land Suitability Score 116-130 (Residential Area) and Land Suitability Score 92-135 (Agriculture Area) are categorized as an obstacle area with various constraints such as water supply, disaster, and others but can still be overcome by artificial engineering. Land Suitability Score <116 (Residential Areas) and Land Suitability Score <92 (Agricultural Area) are limitation area that are not feasible to be used as residential and educational areas, a variety of constraint reduction efforts can be done but require very high cost. Therefore it is suggested  to convert the area into conservation. It is concluded that the best areas to be used as residential and agricultural areas are located in the Banjaran District such as Banjaran, Kamasan, Sindangpanon, and Tarajusari Village.